Tsunami recovery in Sri Lanka : retrospect and prospect - Hettige, S. T. (Siripala T.); University of Colombo. Social Policy Analysis and Research Centre; ActionAid International Sri Lanka (Colombo : Social Policy Analysis and Research Centre in collaboration with ActionAid International, 2007)
Contributed articles presented at the seminar on Tsunami recovery and rehabilitation: accomplishments and drawbacks, 2nd-3rd February, 2007 moderated by SPARC, University of Colombo and ActionAid International, Sri Lanka.
Keywords: Indian Ocean Tsunami, 2004 -- Congresses; Tsunami relief -- India -- Congresses; Disaster victims -- Rehabilitation -- India -- Congresses